Educational Priorires In Kurdish Journalism Brayati Newspaper As Study Sample "Educational And Analytical Study - Haji, Sattar J.; Saeed, Diyar A. (Humanities Journal of University of Zakho, 2016)
The research aims to figure out to what extent Kurdish journalism was concerned about educational issues. For this purpose, the Kurdish newspaper Brayati has been selected as the sample of study. To achieve this objective, a descriptive analytical method has been used to collect facts and data on the current study to be interpreted and analyzed comprehensibly. The research sample consisted of (27) issued papers. After content analysis, the results showed that the newspaper focused on publishing about various educational matters within its pages. For example, calling for education to be in Kurdish language ranked first, the issue of opening schools for eradicating illiteracy on second place, while appointing teachers and building schools in Kurdish remote areas and villages was third and fourth respectively, the issue of educational problems on the fifth place, and the issue of compulsory education on the sixth and last place. In light of study results, the researchers presented a set of recommendations. Most importantly, the need for introducing the educational matters addressed by the Kurdish journalism to the curricula of Contemporary History in colleges of Arts and education in Kurdistan Region, and recommending researchers in the field of education and history to use content analysis from other newspapers in the Kurdish journalism and compare their results with the results of the current study.